Dentigerous Cyst associated with Impacted Supernumerary Maxillary Anterior Tooth - Nair, Preeti; Khare, Pooja (Journal of Orofacial Research, 2013)
Dentigerous cyst (DC) is a common oral lesion formed by fluid accumulation between the fully formed tooth crown and the reduced enamel epithelium. It is associated mostly with  mandibular impacted third molar and rarely with the mesiodens. This is an interesting case report of dentigerous cyst in the presence of full complement of teeth.